Immediate and carry‐over effects of insect outbreaks on vegetation growth in West Greenland assessed from cells to satellite. (28th June 2019) - Prendin, Angela Luisa; Carrer, Marco; Karami, Mojtaba; Hollesen, Jørgen; Bjerregaard Pedersen, Nanna; Pividori, Mario; Treier, Urs A.; Westergaard‐Nielsen, Andreas; Elberling, Bo; Normand, Signe
Abstract: Aim: Tundra ecosystems are highly vulnerable to climate change, and climate–growth responses of Arctic shrubs are variable and altered by microsite environmental conditions and biotic factors. With warming and drought during the growing season, insect‐driven defoliation is expected to increase in frequency and severity with potential broad‐scale impacts on tundra ecosystem functioning. Here we provide the first broad‐scale reconstruction of spatio‐temporal dynamics of past insect outbreaks by assessing their effects on shrub growth along a typical Greenlandic fjord climate gradient from the inland ice to the sea. Location: Nuuk Fjord (64°30′N/51°23′W) and adjacent areas, West Greenland. Taxa: Great brocade ( Eurois occulta L.) and grey willow ( Salix glauca L.). Methods: We combined dendro‐anatomical and remote sensing analyses. Time series of ring width (RW) and wood‐anatomical traits were obtained from chronologies of >40 years established from 153 individuals of S. glauca collected at nine sites. We detected anomalies in satellite‐based Normalized Difference Vegetation Index (NDVI) related to defoliation and reconstructed past changes in photosynthetic activity across the region. Results: We identified outbreaks as distinctive years with reduced RW, cell‐wall thickness and vessel size, without being directly related to climate but matching with years of parallel reduction in NDVI. The two subsequent years after the defoliation showed a significant increase in RW. The reconstructed spatio‐temporal dynamics of these events indicate substantial regional variation in outbreak intensity linked to the climate variability across the fjord system. Main conclusions: Our results highlight the ability of S. glauca to cope with severe insect defoliation by changing carbon investment and xylem conductivity leading to high resilience and rapid recovery after the disturbance. Our multiproxy approach allows us to pinpoint biotic drivers of narrow ring formation and to provide new broad‐scale insight on the C‐budget and vegetation productivity of shrub communities in a widespread arctic ecosystem.